Some clinical and epidemiological observations on virologically confirmed dengue hemorrhagic fever - T. K. Samsi; H. Wulur; D. Sugianto; C. R. Bartz; R. Tan; A. Sie (Paediatrica Indonesiana, 1990)
This study is a part of a one year prospective study on dengue hemorrhagic fever (DHF) carried out in the Department of Pediatrics, Sumber Waras Hospital in West Jakarta. Viral isolation and serologic analysis for DHF were done by Namru-2 in Jakarta. The subjects were 151 virologically confirmed DHF Patients admitted to the Department of Pediatrics during the period of September 1987 - June 1988, consisting of 82 boys and 69 girls of 6 months - 15 years old. The predominant age group was 5 to 9 years, representing 49. 7% subjects. Dengue virus was isolated from sera during the first 8 days of illness and in 139 (42.1%) during the first. 5 days of illness. Dengue virus type 1, 2, 3 and 4 were isolated from 16.6%, 13.2%, 69.5% and 0 . 7% subjects, respectively. The clinical manifestations revealed no striking differences between dengue 3 and others except for thrombocytopenia and shock. High fever, hemoconcentration and thrombocytopenia on admission was observed in 30.5%, 8,6% and 8.6% of subjects, respectively. Dengue shock syndrome (DSS) were observed in 23 (15.2%) with 3 (2%) fatal cases. Dengue virus serotype 3 was observed in 20 out of 23 DSS cases (86,9%) and all fatal cases were associated with dengue type 2. This study revealed that dengue 3 is the predominant virus circulating during recent epidemics and is associated with more severe clinical manifestation and with a higher incidence rate of living area.